2021
DOI: 10.1002/zamm.202000158
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a hollow fiber in thermoelectric materials considering interfacial thermal resistance

Abstract: Hollow fibers are commonly introduced into flexible thermoelectric materials for certain engineering applications. However, significant stress concentration may be caused in the vicinity of the interface between the fibers and thermoelectric matrix threatening the reliability of the composite structure. In this paper, we study the plane deformation problem of a rigid hollow fiber embedded in a thermoelectric material. By utilizing the complex variable method, the closed‐form solutions for electric, thermal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…With the advancement of thermoelectric science and technology, the morphology of weavable thermoelectric materials has become diverse, and the research focus in this field continues to evolve. Generally, research focus areas in weavable thermoelectrics can be categorized as indicated by figure 2, including 1D fibers [42,43, and nanowires (NWs) [167,168], 2D thin films [169][170][171][172], 3D fabrics [173][174][175][176][177][178][179][180][181][182][183][184][185][186], device assembling [42,43,124], simulations [187,188], and integrations [189]. Among them, thermoelectric fibers with typical 1D macroscopic morphologies have garnered significant research attention.…”
Section: Classifications Of Weavable Thermoelectricsmentioning
confidence: 99%
“…With the advancement of thermoelectric science and technology, the morphology of weavable thermoelectric materials has become diverse, and the research focus in this field continues to evolve. Generally, research focus areas in weavable thermoelectrics can be categorized as indicated by figure 2, including 1D fibers [42,43, and nanowires (NWs) [167,168], 2D thin films [169][170][171][172], 3D fabrics [173][174][175][176][177][178][179][180][181][182][183][184][185][186], device assembling [42,43,124], simulations [187,188], and integrations [189]. Among them, thermoelectric fibers with typical 1D macroscopic morphologies have garnered significant research attention.…”
Section: Classifications Of Weavable Thermoelectricsmentioning
confidence: 99%